Pengaruh Penguasaan Bahasa Indonesia dan Inggris terhadap Kemampuan Speaking Mahasiswa STIE LPI Makassar - Suhartina R. (CV. Insight Publisher, 2025)
This study aims to analyze the influence of Indonesian and English language proficiency on the speaking ability of students at STIE LPI Makassar. The study employed a quantitative approach with an explanatory research design. A total of 120 students were selected as samples using proportionate stratified random sampling. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that both Indonesian and English language proficiency have a positive and significant effect on students’ speaking ability, both partially and simultaneously. Indonesian language proficiency shows a more dominant influence compared to English language proficiency. The coefficient of determination (R²) of 0.582 indicates that the two variables explain 58.2% of the variance in students’ speaking ability. These findings highlight that students’ speaking ability is not solely determined by a single language proficiency, but rather by the integration of bilingual competencies. Therefore, higher education institutions should develop integrated language learning strategies to enhance students’ communication skills more effectively.